2012
DOI: 10.1128/jb.00348-12
|View full text |Cite
|
Sign up to set email alerts
|

A Listeria monocytogenes RNA Helicase Essential for Growth and Ribosomal Maturation at Low Temperatures Uses Its C Terminus for Appropriate Interaction with the Ribosome

Abstract: Listeria monocytogenes , a Gram-positive food-borne human pathogen, is able to grow at temperatures close to 0°C and is thus of great concern for the food industry. In this work, we investigated the physiological role of one DExD-box RNA helicase in Listeria monocytogenes . The RNA helicase Lmo1722 was required for optimal growth at low temperatures, whereas it was dispensable at 37°C. A Δ lmo1722 strain was less motile due to downregulation of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…Overall, the results indicate that intact CrhR is required for proper cellular localization. This conclusion is similar to those from studies revealing similar responses to C-terminal deletion of a cold-induced RNA helicase, Lmo1722, which resulted in disassociation from the 50S ribosome in Listeria monocytogenes (38) and removal of CshA from the Staphylococcus aureus degradosome (14). While thylakoid membrane-associated polysomes have been reported in cyanobacteria (42), the subcellular localization of the cyanobacterial degradosome has not been determined (39).…”
Section: Figsupporting
confidence: 73%
See 1 more Smart Citation
“…Overall, the results indicate that intact CrhR is required for proper cellular localization. This conclusion is similar to those from studies revealing similar responses to C-terminal deletion of a cold-induced RNA helicase, Lmo1722, which resulted in disassociation from the 50S ribosome in Listeria monocytogenes (38) and removal of CshA from the Staphylococcus aureus degradosome (14). While thylakoid membrane-associated polysomes have been reported in cyanobacteria (42), the subcellular localization of the cyanobacterial degradosome has not been determined (39).…”
Section: Figsupporting
confidence: 73%
“…Although many prokaryotic DEAD box RNA helicases have roles in ribosome biogenesis (16)(17)(18)38), our polysome fractionation results suggest that this function is unlikely in Synechocystis, as CrhR was detected only in the polysome-containing fraction. In addition, our runoff polysome analysis indicated that CrhR is as- a Warm-grown (30°C) and cold-shocked (20°C for 3 h) cells were viewed using immunoelectron microscopy.…”
Section: Discussionmentioning
confidence: 76%
“…Defects in ribosome biogenesis were already investigated in E. coli. There, deletion of srmB or csdA leads to a decrease in free 50S subunits and accumulation of 40S particles representing incompletely assembled large subunits (14,53). Interestingly, even though we also observe a clear reduction of the 50S subunits, no 40S premature particles were detected.…”
Section: Discussionmentioning
confidence: 65%
“…Involvement of RNA helicases during RNA maturation and degradation has been shown in Escherichia coli (RhlB and RhlE), Bacillus subtilis (CshA, CshB, DeaD, and YfmL), and Staphylococcus aureus (CshA) where they also been shown to associate with RNA degradosome components (14,(16)(17)(18)(19)(20)(21)(22)(23). One RNA helicase in Listeria monocytogenes, Lmo1722, was shown to be important for ribosome biogenesis and interacted with the 50S subunit through its C terminus (6). Not surprisingly, the absence of Lmo1722 and other listerial RNA helicases has the largest effect at low temperatures and under adverse stress conditions (6,15,(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…One RNA helicase in Listeria monocytogenes, Lmo1722, was shown to be important for ribosome biogenesis and interacted with the 50S subunit through its C terminus (6). Not surprisingly, the absence of Lmo1722 and other listerial RNA helicases has the largest effect at low temperatures and under adverse stress conditions (6,15,(24)(25)(26)(27).…”
mentioning
confidence: 99%